2017
DOI: 10.1504/ijscim.2017.086372
|View full text |Cite
|
Sign up to set email alerts
|

A green perspective on capacitated time-dependent vehicle routing problem with time windows

Abstract: This study presents a novel approach to the vehicle routing problem by focusing on greenhouse gas emissions and fuel consumption aiming to mitigate adverse environmental effects of transportation. A time-dependent model with time windows is developed to incorporate speed and schedule in transportation. The model considers speed limits for different times of the day in a realistic delivery context. Due to the complexity of solving the model, a simulated annealing algorithm is proposed to find solutions with hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Li et al [26] took the full set of GHG emissions composed of CO2, CH4 and N2O into account when modeling the green cold chain VRP. Kazemian et al developed a novel model for capacitated VRP model with time-dependent speed limits aiming to minimize two green objectives, total fuel consumption and GHG emission [27].…”
Section: Vehicle Routing Problem With Environmental Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [26] took the full set of GHG emissions composed of CO2, CH4 and N2O into account when modeling the green cold chain VRP. Kazemian et al developed a novel model for capacitated VRP model with time-dependent speed limits aiming to minimize two green objectives, total fuel consumption and GHG emission [27].…”
Section: Vehicle Routing Problem With Environmental Concernsmentioning
confidence: 99%
“…Constraint (26) guarantees that traveling among depots is not allowed, respectively. Constraints (27) and (28) indicate products' balancing flow between two echelon layers. Constraint (29) shows before-mentioned decision variables and parameters are non-negative.…”
Section: Model Establishmentmentioning
confidence: 99%
“…Therefore, in recent years, many scholars have devoted themselves to analyzing the impact of real-time speed (or uncertainty of travel time) caused by traffic congestion on costs or CO 2 emissions. The method adopted is generally to use the segmentation function of speed to simulate traffic congestion [24,[27][28][29][30][31][32][33]. In addition, Poothalir et al [34] used a triangular probability distribution function curve to characterize the time-varying velocity and found that the change in velocity is beneficial for reducing fuel consumption.…”
Section: Macro Model Vp Ft Rg E S √ √ √ √mentioning
confidence: 99%
“…As stated in Barth and Boriboonsomsin [30], when the vehicle velocity is less than 30mph, carbon emission and fuel consumption will nonlinearly grow rapidly; that is, when the vehicle speed decreases from 30mph to 12.5mph or 12.5mph to 5mph, carbon emission and fuel consumption per one mile will be double. The different vehicle velocities are assumed with respect to different times of day to incorporate traffic regulations (Kazemian and Aref) [31] or traffic congestion. Aiming at reflection of speed limits, several main manners were applied and described as follows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aiming at reflection of speed limits, several main manners were applied and described as follows. The first one for representing traffic congestion is featured that different speed or travel time is to formulate it as a step function of time and uses a simple method to obtain continuous travel times (Kuo [15], Xiao et al [28], Kazemian and Aref [31], Mirmohammadi et al [32], Figliozzi [33], Soysal et al [34], Franceschetti et al [35], etc.) or only one speed limit is assigned to a specific vehicle which is traversing a particular arc (Afshar-Bakeshloo et al) [36].…”
Section: Literature Reviewmentioning
confidence: 99%